The Medieval Hospital of Pena Godón: A Glimpse at a Long Forgotten Place in the French Way of Saint James - Valdés Blanco-Rajoy, Rosario (Madrygal. Revista de Estudios Gallegos, 2016)
The key points to the historical evolution of Pena Godón are identical to those that mark the history of monasteries and of various religious and military authorities that settled in the area. They also reflect the relationship of these orders with the nobility, the role played as joint landholders in a system of agrarian exploitation and the impact of all this on the peasants’ way of life. These points also help explain the evolution of the landscape in this part of the French Way where the settlement was located, the history of its hospitals and the people and the institutions that founded and managed them.